Perspective on cystic fibrosis and physical activity: Is there a difference compared to healthy individuals?. Issue 10 (26th July 2016) - Jantzen, Anika; Opoku‐Pare, Miriam; Bieli, Christian; Ruf, Katharina; Hebestreit, Helge; Moeller, Alexander
Summary: Objectives: The aim of this study was to compare habitual physical activity between cystic fibrosis (CF) patients and healthy controls and to investigate possible predictors for reduced physical activity in CF patients. Methods: Sixty‐six patients with CF (3–44 years) and 65 healthy controls (3–55 years) were asked to wear an accelerometer (Actigraph GT1M) for 9 days (at least 10 hr/day). Physical activity was classified in five categories from very low to very strenuous. Results: In general, there was no difference in physical activity between CF patients and healthy controls. However, young school‐aged 6–13 years old children with CF spent less time with strenuous and very strenuous activity than healthy controls (adjusted difference in activity −0.43 (−0.69, −0.17)). Patients with very low lung function were significantly less active, but other CF‐associated conditions did not affect physical activity. Conclusions: While we found similar levels of physical activity measured by accelerometry in patients with CF compared to healthy controls in general, young school‐aged children showed less engagement in strenuous activities than their healthy counterparts. As the reduced physical activity in young school children was not likely to be explained by the disease state, strenuous physical activity may be enhanced by advocating exercise and sport.Pediatr Pulmonol. 2016;51:1020–1030. © 2016 Wiley Periodicals, Inc.